Analisis Faktor yang Mempengaruhi Pengelolaan Obat Publik di Instalasi Farmasi Kabupaten (Studi di Papua Wilayah Selatan) - YOHANES WAHYU WALUYO; UMI ATHIYAH; THINNI NURUL ROCHMAH (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
Public drug management is purposed to ensure availability of quality drug with proper type and quantity, distributed well and orderly. Recent problem of public drug management is the level of drug availability which has not been suitable with the health care need since inadequate supply still occur in one part and oversupply in other part. This research was aimed to indentify what factors are influencing public drug management and to identify public drug management function. This is an observational using cross sectional data collection method, presented descriptively in District Pharmacy Installation and descriptive in nature. Result of research showed that public drug management were influenced by factors such as packing and maintenance funds which is not evenly distributed, staff education which have not met the required need, governance which were not yet performed and drug management facility/ tools which were partially incomplete. The description of drug management are as following: drug procurement fund allocation of 114.02%, drug availability with disease pattern of 170.87%, planning accuracy of 114.02%, essential drug of 70.16%, generic drug of 87.87%,drug procurement has not been met all contract books of 77.00%, drug availability of 75.75%, broken and expired drug of 7.01%, drug vacant time mean of 0.37%, drug distribution accuracy of 57.68% and distributed drug deviation of 17.30%.